Infections increase the risk of developing Sjögren's syndrome. (17th April 2019) - Mofors, J.; Arkema, E. V.; Björk, A.; Westermark, L.; Kvarnström, M.; Forsblad‐d'Elia, H.; Magnusson Bucher, S.; Eriksson, P.; Mandl, T.; Nordmark, G.; Wahren‐Herlenius, M.
Abstract: Objective: Environmental factors have been suggested in the pathogenesis of rheumatic diseases. We here investigated whether infections increase the risk of developing primary Sjögren's syndrome (pSS). Methods: Patients with pSS in Sweden ( n  = 945) and matched controls from the general population ( n  = 9048) were included, and data extracted from the National Patient Register to identify infections occurring before pSS diagnosis during a mean observational time of 16.0 years. Data were analysed using conditional logistic regression models. Sensitivity analyses were performed by varying exposure definition and adjusting for previous health care consumption. Results: A history of infection associated with an increased risk of pSS (OR 1.9, 95% CI 1.6–2.3). Infections were more prominently associated with the development of SSA/SSB autoantibody‐positive pSS (OR 2.7, 95% CI 2.0–3.5). When stratifying the analysis by organ system infected, respiratory infections increased the risk of developing pSS, both in patients with (OR 2.9, 95% CI 1.8–4.7) and without autoantibodies (OR 2.1, 95% CI 1.1–3.8), whilst skin and urogenital infections only significantly associated with the development of autoantibody‐positive pSS (OR 3.2, 95% CI 1.8–5.5 and OR 2.7, 95% CI 1.7–4.2). Furthermore, a dose–response relationship was observed for infections and a risk to develop pSS with Ro/SSA and La/SSB antibodies. Gastrointestinal infections were not significantly associated with a risk of pSS. Conclusions: Infections increase the risk of developing pSS, most prominently SSA/SSB autoantibody‐positive disease, suggesting that microbial triggers of immunity may partake in the pathogenetic process of pSS. Abstract :